Mechanisms underlying mechanical sensitization induced by complement C5a: the roles of macrophages, TRPV1, and calcitonin gene-related peptide receptors. Issue 3 (March 2019) - Warwick, Charles A.; Shutov, Leonid P.; Shepherd, Andrew J.; Mohapatra, Durga P.; Usachev, Yuriy M.
Abstract : Abstract: The complement system significantly contributes to the development of inflammatory and neuropathic pain, but the underlying mechanisms are poorly understood. Recently, we identified the signaling pathway responsible for thermal hypersensitivity induced by the complement system component C5a. Here, we examine the mechanisms of another important action of C5a, induction of mechanical hypersensitivity. We found that intraplantar injection of C5a produced a dose-dependent mechanical sensitization and that this effect was blocked by chemogenetic ablation of macrophages in both male and female mice. Knockout of TRPV1 or pretreatment with the TRPV1 antagonists, AMG9810 or 5′-iodoresiniferatoxin (5′-IRTX), significantly reduced C5a-induced mechanical sensitization. Notably, local administration of 5′-IRTX 90 minutes after C5a injection resulted in a slow, but complete, reversal of mechanical sensitization, indicating that TRPV1 activity was required for maintaining C5a-induced mechanical hypersensitivity. This slow reversal suggests that neurogenic inflammation and neuropeptide release may be involved. Indeed, pretreatment with a calcitonin gene-related peptide (CGRP) receptor antagonist (but not an antagonist of the neurokinin 1 receptor) prevented C5a-induced mechanical sensitization. Furthermore, intraplantar injection of CGRP produced significant mechanical sensitization in both wild-type and TRPV1 knockout mice. Taken together, these findings suggest that C5a produces mechanical sensitization by initiating macrophage-to-sensory-neuron signaling cascade that involves activation of TRPV1 and CGRP receptor as critical steps in this process. Abstract : The complement system component C5a produces mechanical hypersensitivity by initiating macrophage-to-nociceptor signaling cascade that involves activation of TRPV1 and calcitonin gene-related peptide receptor as critical steps in this process.